Retrospective Review of Atypical Femoral Fracture in Metastatic Bone Disease Patients Receiving Denosumab Therapy. (April 2017) - Yang, Samantha Peiling; Won B. Kim, Tae; Boland, Patrick J.; Farooki, Azeez
Abstract: Background: Denosumab therapy is used to reduce skeletal‐related events in metastatic bone disease (MBD). There have been reports of atypical femoral fracture (AFF) in osteoporotic patients treated with denosumab but none in the context of higher dose and more frequent denosumab therapy for MBD. The goal of this study was to assess the incidence of AFF in MBD. Patients and Methods: We conducted a retrospective review of 253 patients who received a minimum of 12 doses of denosumab at 120 mg each for MBD. To identify patients with asymptomatic atypical stress reactions in the lateral subtrochanteric femur (which precede fractures), we reviewed the skeletal images of 66 patients who had received at least 21 doses of denosumab for AFF features. Results: These patients received a median of 17 doses, with a median treatment duration of 23 months. There was 1 case of undiagnosed clinical AFF detected after chart review and 2 cases of subclinical atypical femoral stress reaction observed on imaging review after 23 doses of denosumab over 33 months, 28 doses over 27 months, and 21 doses over 21 months, respectively. Scout computed tomography films showed diffuse cortical thickening of diaphysis with localized periosteal reaction of lateral femoral cortex. Bone scan and magnetic resonance imaging scan of 2 patients with stress reactions confirmed the diagnosis. Conclusion: The incidence of clinical AFF in this context is 0.4% (1/253; 95% confidence interval [CI] 0.1%–2.2%), and the incidence of atypical femoral stress reaction based on imaging review is 4.5% (3/66; 95% CI 1.6%–12.5%). Clinicians should be aware of the clinical prodrome (which may or may not be present) and antecedent imaging changes associated with AFF. The Oncologist 2017;22:438–444 Implications for Practice: Among patients with metastatic bone disease treated with denosumab, cases of clinical and subclinical atypical femoral fracture (AFF) are rare. The one detected case of clinical fracture went unrecognized despite prodromic symptoms. Clinicians should be aware of (a) the potential prodrome of anterior thigh/groin pain and (b) subclinical imaging changes in the lateral femur, both of which may precede clinical AFF.